Ecology of common bully ( Gobiomorphus cotidianas ) in the Tarawera and Rangitaiki rivers: Isolation by inland distance or anthropogenic discharge? - Natalie A. Bleackley; Michael J. Landman; Nicholas Ling (New Zealand Journal of Marine and Freshwater Research, 2009)
Previous research has identified distinct genetic, life‐history and reproductive differences between populationsof common bully ( Gobiomorphus cotidianus ) upstream and downstream of a pulp and paper mill outfall on the Tarawera River in the Bay of Plenty, New Zealand. This study investigated the distribution of common bully in the Tarawera River by examining fish collected from upstream (37 km inland) and downstream (20 km inland) locations and comparing them to fish from similar inland locations (40 km and 17 km inland, respectively) in the nearby Rangitaiki River. Reproductive divergence was observed between upstream and downstream sites of both rivers by differing annual trends in gonadosomatic index. Stable carbon and nitrogen isotopes confirmed residency at each sampling site and otolith microchemistry demonstrated different life‐history strategies between upstream and downstream populations. Diadromous recruits dominated in both downstream river populations, with a general disappearance of diadromy upstream. A mixture of diadromous and non‐diadromous fish were found in the upstream Rangitaiki River, whereas diadromous recruits were absent in the upstream Tarawera River. A reduction in oculoscapular canal structures also coincided with loss of diadromy in fish from both rivers. A behavioural study to determine whether pulp and paper mill effluent may deter fish migration within the Tarawera River demonstrated a strong avoidance of effluent, but only at concentrations (>25%) greater than those that naturally occur in the river (